THE EFFECT OF LEADERSHIP, POSITIVE WORK ENVIRONMENT, GROWTH, AND BASIC NEEDS TO MEMBER ENGAGEMENT IN STUDENT ASSOCIATION AS NON-PROFIT ORGANIZATIONS - Rindu Fadilah Amor Syahir (Jurnal Pijar, 2023)
The sustainability existence of the student association is highly dependent on the contributions made by its members in running the wheels of activity in each period. It is very necessary for each student association to understand the condition of engagement of each member by conducting regular analysis. It does not rule out the possibility that the condition of member engagement with the organization can change along with the dynamics of the internal conditions of the organization that occur due to certain factors. Currently, very limited studies examine the conditions of engagement of members of non-profit organizations, especially student associations. Therefore, this study aims to investigate the conditions and factors that influence member engagement with the object of research in three student associations located at the Bandung Institute of Technology. This research uses qualitative methods through semi-structured interviews involving 15 people as informants. Each informant comes from a different level (managerial/staff), division and has different characteristics. The interview results show that there are four factors that influence the engagement of student association members, consist of: Leadership, Positive Work Environment, Growth, and Basic Needs. These four variables can directly affect the engagement condition of student association members both positively and negatively